Gyrification Index and Encephalizaton Quotient of Brain of Surti Buffalo (Bubalus bubali - Suman, Alka; Pandey, Sweta (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The brain of Surti buffaloes presents many cortical foldings. These are called gyrification. In the present study on brain of 12 Surti buffaloes, the folded cerebral hemispheres presented various sulci and gyri of different sizes. Gyrification Index (GI) was measured by the sum of the complete exposed surface and superficially exposed surface of cerebral cortex. The overall mean value of gyrification index of both of cerebral hemispheres was 2.52±0.02. The Encephalization Quotient (EQ) is the ratio of brain mass to body mass, which gives rough estimate of the intelligence of the Surti buffaloes. The overall mean value of encephalization quotient of Surti buffaloes was found to be 0.74. cranium. In most mammals, gyrification begins The Surti is a breed of water buffalo found in the Charottar tract of Gujarat between the Mahi and Sabarmati rivers. The best animals of this breed are found in Anand, Kaira and Baroda districts of Gujarat (Banerjee, 2014). The surface of the cerebral cortex is marked by thick ridges the gyri cerebri, separated by binding grooves the sulci. The gyrification is the specific pattern formed by the different sulci and gyri of cerebral cortex (Mayhew et al., 1995). Gyrification allows a large cortical surface area and hence greater cognitive functionality to fit inside a smaller during fetal development (Rakic, 2009). Intelligence may be defined by the speed and success of how animals solve problems to survive in their natural and social environments (Roth and Dicke, 2005). The brain is considered to be the carrier of intelligence.